RETRACTED: The impact of high-quality development of rural logistics on consumption: energy and healthcare consumption as an example - Tang, Liqiang; Wang, Weijing; Bi, Wentai (Frontiers in Energy Research, 2024)
The creation of infrastructure in rural areas is an essential guarantee for the economic development and in improving farmers' living standards. As a critical link between urban and rural production and consumption, rural logistics is essential to maximize the efficiency of rural infrastructure investment. Based on the panel data of 31 provinces in China from 2011-2020, the study analyzes the impact of high-quality development of rural logistics on the enhancement of residents' consumption in terms of scale and quality, using a fixed-effects model. Results suggest that this development promotes the growth of rural residents' consumption and quality, with a noticeable regional heterogeneity. The most significant effect is observed in the eastern region. Further analysis shows that inland and less developed provinces of rural e-commerce stimulate residents' consumption upgrade with the help of high-quality development of rural logistics at a level weaker than coastal provinces and developed provinces of rural e-commerce. Consequently, it is recommended to boost the building of logistics infrastructure in rural areas and actively cultivate diversified rural logistics operators in the western and northeastern regions. The contribution of this study is to examine the impact of rural logistics on rural residents' consumption from the perspective of infrastructure, further validating the role of infrastructure development in promoting economic growth.